Vocabulary Learning among less proficient young adults using children’s stories1 - Radzuwan, Ab Rashid (2011)
The main purpose of this study was to investigate whether stories originally written for children could be used to develop vocabulary learning among young adults who are less proficient in the English language. This study was also carried out to explore the perceptions of these not so proficient students and their teacher regarding the use of children’s stories in developing vocabulary learning. The study involved 15 students in a secondary school in Kelantan, Malaysia. All of the students were 14 years of age and had learned English as their second language. This study employed a one group pre-test and post-test experimental design. Triangulation, involving semi-structured interviews and written accounts in learning diaries, was used. Findings showed that children’s stories did contribute to the development of vocabulary learning among less proficient young adult learners. The use of children’s stories in developing vocabulary learning among less proficient young adult learners was also perceived positively by both the learners and the teacher as determined by the interviews.